1988
DOI: 10.1111/j.1911-3846.1988.tb00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditors' usage of unaudited book values when making presampling audit value estimates*

Abstract: Abstract. An important issue in audit judgment research concems auditors' use of unaudited book values when making judgments in the presampling phase of the audit. This paper presents a rudimentary model of the auditor's belief revision process with respect to unaudited book values from an audit value estimation perspective. An experiment testing some implications of the model is also presented. The model proposes that the auditor should judge the validity of unaudited book values in the circumstances and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
0
4
0
2
Order By: Relevance
“…The commonality of focus on gross profit helps compare conclusions across studies, but reduces the generalizability of results to other accounts. This point is especially important given that Shields et al (1988) and Asare and Davidson (1995) found differences in error estimation judgments across accounts.…”
Section: Notesmentioning
confidence: 93%
See 2 more Smart Citations
“…The commonality of focus on gross profit helps compare conclusions across studies, but reduces the generalizability of results to other accounts. This point is especially important given that Shields et al (1988) and Asare and Davidson (1995) found differences in error estimation judgments across accounts.…”
Section: Notesmentioning
confidence: 93%
“…Neither Biggs and Wild (1985) nor Heintz and White (1989) contained indications that data reliability might be suspect. Case materials of Shields et al (1988) contained indications of audit risk (e.g., increased competition in the client's industry, past audit adjustments, electronic data processing system inadequacy) but this information was common to all experimental conditions. Similarly, McDaniel and Kinney (1995) used rich case materials, but did not vary data reliability.…”
Section: Prior Research and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditors who receive unaudited values with material errors are less accurate than auditors who do not receive these anchors (Shields et al 1988).…”
Section: Evaluation Of Evidencementioning
confidence: 99%
“…Biggs en Wild, 1985Shields, Solomon en Waller, 1988Heintz en White, 1989Wild en Biggs, 1990Heintz, White en Bedard, 1995Vaassen en Hassink, 1995 Cijferanalyses die betrekking hebben op een meer gedetailleerde periode leiden tot zinvollere en betrouwbaardere analyse.…”
Section: Kinney En Uecker 1982unclassified